DIAGNOSTIC ACCURACY OF MRI FOR THE DIAGNOSIS OF RECTAL CARCINOMA TAKING HISTOPATHOLOGY AS GOLD STANDARD - ANSARI, MA; TAHIR, MM; KHALID, D; MALIK, RA; KHAN, U; HUSSAIN, S; SHAMIM, B; SHOUKAT, S; MUSTAFA, K; ANSARI, M (Biological and Clinical Sciences Research Journal, 2024)
Rectal carcinoma is a major contributor to colorectal cancer-related morbidity and mortality worldwide. Accurate diagnosis is essential for appropriate treatment planning and improved patient outcomes. Magnetic resonance imaging is widely used for the evaluation of rectal carcinoma due to its excellent soft-tissue contrast and multiplanar imaging capabilities. However, local data regarding its diagnostic accuracy using histopathology as the gold standard are limited. Objective: To determine the diagnostic accuracy of magnetic resonance imaging in the diagnosis of rectal carcinoma, taking histopathology as the gold standard. Methods: This cross-sectional observational study was conducted in the Departments of Diagnostic Radiology at Liaquat National Hospital and Jinnah Postgraduate Medical College, Karachi, over a period of six months from 1 January 2024 to 6 July 2024. A total of 174 patients aged 25 to 60 years with clinical suspicion of rectal carcinoma were included using non-probability consecutive sampling. Magnetic resonance imaging was performed using high-resolution T2-weighted sequences. MRI findings were compared with histopathological results. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were calculated using a two-by-two contingency table. Results: Out of 174 patients, magnetic resonance imaging detected rectal carcinoma in 82 patients (47.1%), while histopathology confirmed rectal carcinoma in 76 patients (43.7%). True positive cases were 68, true negative cases were 86, false positive cases were 14, and false negative cases were 6. Magnetic resonance imaging showed a sensitivity of 91.9%, specificity of 86.0%, positive predictive value of 82.9%, negative predictive value of 93.5%, and an overall diagnostic accuracy of 88.5%. Diagnostic performance remained consistent across different demographic and clinical subgroups. Conclusion: Magnetic resonance imaging demonstrates high diagnostic accuracy for rectal carcinoma compared with histopathology. MRI is a reliable and effective imaging modality for evaluating patients with suspected rectal carcinoma and should be routinely utilized in clinical practice.